Market power, efficiencies, and entry: Evidence from an airline merger - Kai Hüschelrath; Kathrin Müller (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We investigate the competitive effects of the merger between Delta Air Lines and Northwest Airlines (2009) in the domestic U.S. airline industry. Applying fixed effects regression models we find that the transaction led to short term price increases of about 11 percent on overlapping routes and about 10 percent on routes which experienced a merger-induced switch of the operating carrier. Over a longer period, however, our analysis reveals that both merger efficiencies and post-merger entry by competitors initiated a downward trend in prices leaving consumers with a small net price increase of about 3 percent on the affected routes.
urn:nbn:de:bsz:180-madoc-326227
Keywords: L40; L93; 330; airline industry; merger; market power; efficiencies; entry-inducing effects; Luftverkehrsgesellschaft; Fusion; Marktmacht; Fahrpreis; Wirtschaftliche Effizienz; Markteintritt; USA